Primary Neuroendocrine Carcinoma of Sinonasal Tract Infiltrating Maxilla - Zahra, Kanwal; Khurshid, Shaista; Khalid, Ahmareen; Tanwani, Ashok Kumar (International Journal of Pathology, 2018)
Objective: Report an unusual case of primary neuroendocrine carcinoma of sinonasal tract involvingmaxilla.Background: Neuroendocrine tumors are rare in head and neck region and pose a challenge in regardof pathologic diagnosis. Neuroendocrine carcinoma of sinonasal tract is extremely uncommon tumorand despite aggressive management strategies it carries a poor prognosis with a high risk of localrecurrence or distant metastases. Very few cases of sinonasal neuroendocrine carcinoma have beenreported till date.Case Presentation: A 35year female resident of Rawalpindi presented with slowly growing expansileswelling of left maxilla since two and a half years. Initial biopsy was labeled as fibrous dysplasia. Wereceived a maxillectomy specimen. After reviewing the morphology on H&E slides and with help ofimmunohistochemistry she was diagnosed with sinonasal neuroendocrin carcinoma (moderatelydifferentiated) infiltrating maxilla. Patient is now on palliative chemoradiotherapy.Conclusion: Neuroendocrine carcinoma is a rare entity in head and neck region especially in sinonasalarea. It is important to recognize their morphology and pattern of growth because they cannot bemistaken with more common tumors of this area e.g squamous cell carcinoma (poorly differentiated),sinonasal undifferentiated carcinoma (SNUC) and olfactory neuroblastoma.